2021
DOI: 10.3390/su13042081
|View full text |Cite
|
Sign up to set email alerts
|

The Formulation of Epidemic Prevention Work of COVID-19 for Colleges and Universities: Priorities and Recommendations

Abstract: As the Coronavirus disease 2019 (COVID-19) epidemic spreads all over the world, governments of various countries are actively adopting epidemic prevention measures to curb the spread of the disease. However, colleges and universities are one of the most likely places for cluster infections. The main reason is that college students have frequent social activities, and many students come from different countries, which may very likely cause college campuses to be entry points of disease transmission. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…When we look at the studies on COVID-19 in the context of the universities, in general, issues such as the reliability of the measures taken, the reasons for the increase in cases, the examination of the course of the epidemic, simulation studies, risk management, and the effect on the physical and mental health of the students are emphasized. Hsu et al ( 2021 ), using the Bayesian BWM method, which is similar to our study, created a questionnaire with five main and 36 sub-criteria in the light of the expert opinion. Then, this questionnaire was filled out by experts, and the final results were obtained.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…When we look at the studies on COVID-19 in the context of the universities, in general, issues such as the reliability of the measures taken, the reasons for the increase in cases, the examination of the course of the epidemic, simulation studies, risk management, and the effect on the physical and mental health of the students are emphasized. Hsu et al ( 2021 ), using the Bayesian BWM method, which is similar to our study, created a questionnaire with five main and 36 sub-criteria in the light of the expert opinion. Then, this questionnaire was filled out by experts, and the final results were obtained.…”
Section: Discussionmentioning
confidence: 97%
“…Another similar study, Greenhalgh et al ( 2021 ), suggested basic control methods for a safe return to campus against the pandemic. Hsu et al ( 2021 ) in a study they conducted with Bayesian BWM to prevent epidemics on campuses, extensive disinfection of the environment, isolation of contacts, and ventilation are among the most important criteria. Similarly, Chen and O’Keeffe ( 2020 ) in Taiwan state that it is necessary to pay attention to factors such as hygiene, contact tracing, social distance, and ventilation in order for universities to open safely.…”
Section: Discussionmentioning
confidence: 99%
“…In the third step, the problem was made applicable to BBWM with a probabilistic perspective after evaluating according to the original BWM proposed by Rezaei ( 2015 ). The implementation steps are presented in the following with an acceptable level of detail (Hsu et al 2021 ; Mohammadi and Rezaei, 2020b ) and presented in Fig. 3 .…”
Section: Methodsmentioning
confidence: 99%
“…In Gul and Yucesan ( 2021 )’s study, a university ranking model is proposed for the Turkish higher education system by BBWM-TOPSIS integrated model. On the other side, Hsu et al ( 2021 ) proposed a framework of epidemic prevention work and further explored the importance and priority of epidemic prevention works of COVID-19 by BBWM. Table 2 also demonstrates the previous studies on BBWM summarizing application areas and novelties of each one.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the BBWM method is a relatively new MCDM method, it has not been applied to many areas in the literature. However, it has been applied to fields such as information technology and management (Liang et al 2022 ; Abkenar et al 2022 ; Mohammadi and Rezaei 2020b ), supply chain, and logistics management (Munim et al 2022 ; Kelly et al 2022 ; Liu et al 2021 ; Li et al 2020 ), transportation (Huang et al 2021 ), disaster management (Yanilmaz et al 2021 ), risk assessment and management (Tusher et al 2022 ; Ak et al 2022 ), manufacturing (Alkan et al 2022 ), water resource management (Dogani et al 2020 ), tourism (Yang et al 2020 ), and education (Gul and Yucesan 2021 ; Hsu et al 2021 ) with the advantage of eliminating information loss in group decision-making. It is used either as singleton or in conjunction with an auxiliary MCDM method in many practical applications.…”
Section: Literature Reviewmentioning
confidence: 99%